Highly Efficient Flexible Perovskite Solar Cells through Pentylammonium Acetate Modification with Certified Efficiency of 23.35 - Gao, Danpeng; Li, Bo; Li, Zhen; Wu, Xin; Zhang, Shoufeng; Zhao, Dan; Jiang, Xiaofen; Zhang, Chunlei; Wang, Yan; Li, Zhenjiang; Li, Nan; Xiao, Shuang; et al. (Advanced materials (Weinheim), 2023)
Among the emerging photovoltaic technologies, rigid perovskite solar cells (PSCs) have made tremendous development owing to their exceptional power conversion efficiency (PCE) of up to 25.7%. However, the record PCE of flexible PSCs (≈22.4%) still lags far behind their rigid counterparts and their mechanical stabilities are also not satisfactory. Herein, through modifying the interface between perovskite and hole transport layer via pentylammonium acetate (PenAAc) molecule a highly efficient and stable flexible inverted PSC is reported. Through synthetic manipulation of anion and cation, it is shown that the PenA+ and Ac− have strong chemical binding with both acceptor and donor defects of surface‐terminating ends on perovskite films. The PenAAc‐modified flexible PSCs achieve a record PCE of 23.68% (0.08 cm2, certified: 23.35%) with a high open‐circuit voltage (VOC) of 1.17 V. Large‐area devices (1.0 cm2) also realized an exceptional PCE of 21.52%. Moreover, the fabricated devices show excellent stability under mechanical bending, with PCE remaining above 91% of the original PCE even after 5000 bends. Highly efficient and stable flexible inverted perovskite solar cells are developed through modifying the interface between perovskite and hole transport layer via pentylammonium acetate molecule, which achieve a record power conversion efficiency of 23.68% (0.08 cm2, certified: 23.35%) and excellent mechanical stability.